AKIBAT HUKUM PERKAWINAN YANG TIDAK DICATATKAN KETIKA SALAH SATU PIHAK MENINGGAL DUNIA MENURUT UNDANG -UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM - MUHAMMAD RACHARDI (PREMISE LAW JURNAL, 2015)
A legitimate marriage is a registered marriage as it is stipulated in Article 2, paragraph 2 of Law No. 1/1974 on Marriage which states that “every marriage is registered according to the prevailing regulation.” Registration of a marriage is very important as written evidence in bringing a marriage case before a Religious Court. The research used judicial normative and descriptive analytic methods. The data were gathered by using secondary data which consisted of primary, secondary, and tertiary legal materials as the main data. The gathered data were processed, analyzed, and interpreted logically, systematically, and deductively. . The verdict in the Religious Court No. 111/Pdt/2014/PA, Medan, Article 7, paragraph 3 states that the Religious Court only handles the case concerning the marriage which occurs before Law No. 1/1974 on Marriage is in effective. The verdict in Article 14 of the Compilation of the Islamic Law states that the requirements for a marriage are as follows: there are a bide and a groom, a wali nikah (male next of kin and guardian whose consent is required for the marriage of a girl or a woman; he represents her, in person or in writing before the ‘penghulu’), two witnesses, and ijab-qabul (signing a marriage contract). Based on these two verdicts, it could be concluded that the judge has the right to promulgate law in concreto Keywords: Marriage, Unregistered, One of the Couple Dies